(untitled) (CIPEEX, 2025)
The Cerrado is one of the world’s most biodiverse tropical savannas, hosting about 837 bird species, many of them endemic. However, the biome has undergone intense environmental degradation due to agricultural expansion, deforestation, and frequent fires, leading to habitat loss and fragmentation. This study aimed to investigate the biodiversity loss of Cerrado avifauna by identifying the conservation status, population trends, and main anthropogenic pressures affecting native species. A dataset was compiled from secondary information provided by international and national databases (IUCN, MMA/ICMBio, BirdLife International, WikiAves), including attributes such as threat category, population trend, ecological traits, and foraging strategies. The descriptive and comparative analyses revealed that 33 species (3.9%) are listed as threatened globally by the IUCN, while 239 (28.6%) are included in the Brazilian Red List. Moreover, 55.7% of the evaluated species showed decreasing population trends, highlighting a generalized decline. In terms of ecology, most threatened species are insectivores and omnivores with terrestrial foraging habits, which are highly sensitive to the degradation of understory vegetation. Aquatic species, such as the Brazilian merganser (Mergus octosetaceus), are strongly impacted by dam construction and river impoundments, while nectarivores and frugivores are negatively affected by the replacement of native vegetation with exotic monocultures. These findings indicate that Cerrado birds dependent on soil resources and native flora are the most exposed to anthropogenic threats. In conclusion, despite a relatively small proportion of species being globally recognized as threatened, the high percentage of declining populations reflects the severe impact of habitat conversion on the Cerrado biome. These results reinforce the urgent need for integrated conservation actions, including habitat restoration, fire control, and the establishment of ecological corridors, to preserve the unique biodiversity of this tropical savanna.